Low-carbohydrate diet and its influence on visceral fat and other selected physical parameters - Šimková, Simona (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
Low-carbohydrate diets are often a controversial issue. They are not only currently a popular diet method, but also significantly beneficial for health. The influence on the reduction of the total body weight can be very significant, as can the amount of body fat or visceral fat – which is the main risk factor for developing cardiovascular and metabolic diseases. The research in this area is limited. Respondents often fail to finalize it and the studies often include few respondents and are short-term. This article summarizes the published data that focus on the influence of low-carbohydrate diets on visceral fat in the human organism. The goal was to determine which physiological parameters were influenced by this type of diet and how low-carbohydrate diet influences the selected parameters. The results of individual studies are often optimistic, but there are some references to a negative influence of low-carbohydrate diets. Regardless, mostly statistically significant changes in body weight drops have been observed (BMI drops as well), as well as total body fat drop, visceral fat drop, waist circumference drop, and the risk of cardiometabolic diseases. However, it is necessary to continue these studies and especially assess the long-term effect.
Keywords: Anthropometric indicators; Carbohydrates; Cardiometabolic risk factors; Low-carbohydrate diet; Nutrition; Visceral fat